Analysis Of The Comparative Islamic Economic Thinking Between Abu Yusuf, Ibnu Taimiyah And Ibnu Khaldun - Aini, Qurratul (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2021)
Islam has given much thought to the theory of the islamic economy such as ABU Joseph, ibn taimiyah and ibn khaldun of the three figures, before even the conventional economy presents the theory. In this study the authors would like to examine the differences and similarities between the thinking of Joseph's ashes, ibn taimiyah and ibn khaldun. Because the study examines the thoughts of former figures whose data are derived from such regulars as scientific books, scientific journals and web scientific studies make it a library study. The results show that the equations of ABU yusuf, ibn taimiyah, and ibn khaldun are both focused on public finance and the price mechanesme. And ibn taimiyah and ibn khaldun besides focusing on public finance and equal-price mechanisms are also focused on the concept of money. The difference in ABU Joseph's mind is that he does not focus on the concept of money, the role of hisbah and the theory of production, and ibn taimiyah does not focus on the theory of production, and ibn khaldun does not focus on the role of hisbah.